1992
DOI: 10.1128/jvi.66.9.5290-5297.1992
|View full text |Cite
|
Sign up to set email alerts
|

A continuous sequence of more than 70 amino acids is essential for antibody binding to the dominant antigenic site of glycoprotein gp58 of human cytomegalovirus

Abstract: Antigenic domain 1 (AD-1) on glycoprotein gp58 of human cytomegalovirus was characterized in detail, using mouse and human monoclonal antibodies as well as human convalescent sera. Series of procaryotically * Corresponding author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Construction of the expression plasmid coding for complete gB has been described previously [32]. Carboxyterminal truncated forms of gB were expressed using pcDNA3 as plasmid.…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction of the expression plasmid coding for complete gB has been described previously [32]. Carboxyterminal truncated forms of gB were expressed using pcDNA3 as plasmid.…”
Section: Plasmidsmentioning
confidence: 99%
“…Three antigenic domains (AD) have been described previously. AD-1 consists of approximately 80aa between positions 560 and 640 of gB of HCMV strain AD169 [32]. It is the immunodominant region of gB since nearly all sera from HCMV-infected individuals recognize AD-1 [33].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, data have been reported by Wagner et al [29] suggesting the presence of a conformational epitope in AD1. On the basis of experiments mainly performed with gp58fusion fragments, they reported that the minimal sequwce required for binding of AD1-specific antibodies consists ' of more than 70 amino acids; competition experiments performed with synthetic peptides failed to detect any ability of overlapping 20-amino-acid peptides to inhibit the binding of one neutralizing monoclonal antibody to a gp58-fusion protein.…”
Section: Discussionmentioning
confidence: 84%
“…The presence of a strong human-antibody response, with both HCMV' and EBV' human sera, against the sequence TVDSMIALDI (positions 643 -652) is clearly evident; it has to be emphasized that that this major antibody-binding fragment is not included in the region covered by the set of peptides used in previous studies [29]. Several examples of monoclonal antibodies and animal sera recognizing HSV gB and the corresponding proteins of other herpes viruses have been described [20].…”
Section: Discussionmentioning
confidence: 98%
“…Among these, antigenic domain 1 (AD-1), located around amino acid residue 616, constitutes the major site of recognition by neutralizing antibodies (12). Using fusion proteins expressed in Escherichia coli and synthetic peptides, Wagner et al reported that a continuous sequence of more than 70 amino acids between residues 552 and 630 is essential for antibody binding to AD-1 (13). Furthermore, a strong correlation between the neutralization titer of CMV and antibody levels against AD-1 was observed (5).…”
mentioning
confidence: 99%